Direct and indirect in vitro regeneration of Vanilla odorata C. Presl. and V. pompona Schiede, two aromatic species with potential relevance for future vanillin production - Warner Pineda, Jorge (2023)
Direct and indirect shoot regeneration in Vanilla odorata and indirect for V. pompona are described for the first time. Both species produce fragrant, vanillin-containing seed pods and are closely related to the commercially cultivated V. planifolia. Stem nodal segments cultured on Murashige and Skoog medium containing 2.0 mg l−1 6-benzyl aminopurine (BAP) and 1.0 mg l−1 indole butyric acid (IBA) showed > 75% bud sprouting. Media containing 1.0 mg l−1 BAP or thidiazuron (TDZ) in combination with 0.5–1.0 mg l− 1 IBA produced approximately eight shoots/explant. In callus induction experiments, we found that shoot tips from in vitro plantlets were more responsive than leaf and nodal explants with the highest callus induction (47% in V. odorata and 40% in V. pompona) when cultured in the dark on medium containing 2.0 mg l−1 naphthalene acetic acid (NAA) and 1.0 mg l−1 BAP. Calluses transferred to basal medium containing 3.0 mg l−1 BAP plus 1.0 mg l−1 NAA and grown under a 16 h photoperiod produced an average of 4.1 and 3.5 shoots per callus segment for V. odorata and V. pompona, respectively, eight weeks after culture initiation. Histological analysis revealed the presence of calcium oxalate raphides, as confirmed by Raman microscopy, in callus cultured under both dark and light conditions. Over 90% of the plantlets derived from axillary buds exhibited spontaneous root formation on multiplication media; similar to that observed when shoots originating from callus were cultured on plant growth regulator-free medium. During the subsequent greenhouse acclimatization phase, which took place 12 weeks after the final subculture, these plantlets achieved a survival rate of 95%. The results of the present study will be helpful for further large-scale mass propagation efforts of V. odorata and V. pompona and other biotechnological applications such as protoplast isolation.